Peristaltic pump-assisted zirconium nanoparticle-based pipette-tip solid phase extraction for the determination of cobalt by slotted quartz tube-flame atomic absorption spectrophotometry - Tekin, Zeynep; Borahan, Tulay; Ozdogan, Nizamettin; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2020)
In this work, a novel, efficient, simple and green solid phase extraction (SPE) method based on a pipette tip filled with zirconium nanoparticles (Zr-NPs) was developed for the sensitive determination of cobalt in soil samples via slotted quartz tube-flame atomic absorption spectrophotometry (SQT-FAAS). Zirconium nanoparticles providing repeatable and reproducible signals of the analyte were synthesized via a practical method and used as adsorbents. Extraction and preconcentration steps were performed in a customized pipette tip loaded with zirconium nanoparticles. All parameters having significant effects on the analyte signal (pH and volume of the buffer, amount of nanoparticles, type, concentration and volume of the eluent, sample volume and sample flow rate) and instrumental conditions were optimized to obtain the best experimental outcomes. Under the optimum conditions, the linear range of the developed method was found to be between 7.5 and 75 mu g L-1 with a correlation coefficient of 0.9998. The SPE method offered 56-fold enhancement in the detection power of FAAS with the limits of detection and quantification (LOD/LOQ) calculated as 2.2 and 7.2 mu g L-1, respectively. The developed method was applied to soil samples in order to test both its applicability and accuracy for real samples. The percent recoveries obtained were in the range of 90-101%, indicating the method's accuracy and applicability for complex matrices such as soil samples.
Keywords: LIQUID-LIQUID MICROEXTRACTION; WATER SAMPLES; ORGANOPHOSPHORUS PESTICIDES; ONLINE PRECONCENTRATION; NICKEL; SOLVENT; IONS; SPECTROMETRY; SOIL; SOLIDIFICATION; Chemistry; Food Science & Technology; Spectroscopy